Manual de procesos administrativos para panadería y pastelería Faggioni - Mendoza Lindao, Juan Cristóbal (2019)
In most family businesses, there are certain shortcomings such as: the lack of implementation of management tools because they do not have a strategic direction that allows them to plan, coordinate, direct and control the different situations and activities in their daily tasks. This leads to a decline in the recognition and positioning acquired to date in the competitive market. In view of this situation, as part of the research approach, a mixed design (qualitative and quantitative) was established, which allowed conducting a series of surveys of the company's collaborators, and interviews with experts on the subject. In addition, the field study was designed where the situation through which the organization crosses was made known; thus establishing the most outstanding features in the administrative field of the company since not only should it provide excellent customer service and offer high quality handcrafted products, but also should use and take advantage of the latest resources and technologies…………